1999
DOI: 10.1146/annurev.psych.50.1.471
|View full text |Cite
|
Sign up to set email alerts
|

LIFESPAN PSYCHOLOGY: Theory and Application to Intellectual Functioning

Abstract: The focus of this review is on theory and research of lifespan (lifespan developmental) psychology. The theoretical analysis integrates evolutionary and ontogenetic perspectives on cultural and human development across several levels of analysis. Specific predictions are advanced dealing with the general architecture of lifespan ontogeny, including its directionality and age-differential allocation of developmental resources into the three major goals of developmental adaptation: growth, maintenance, and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

44
773
1
52

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 1,025 publications
(870 citation statements)
references
References 170 publications
44
773
1
52
Order By: Relevance
“…Previous research has suggested that an individual's approach to life circumstances alters with age [7,17,18], and this is largely supported here. Within the LBC1921, the number of predictors for each of the QoL measures is lower than within the LBC1936.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous research has suggested that an individual's approach to life circumstances alters with age [7,17,18], and this is largely supported here. Within the LBC1921, the number of predictors for each of the QoL measures is lower than within the LBC1936.…”
Section: Discussionsupporting
confidence: 75%
“…There has been a paucity of research amongst older age groups; those investigating older old age have suggested an accelerated decline in QoL [14], possibly due to a reduction in cognitive resources available for compensatory strategies [15]. Baltes and colleagues applied a lifespan approach to ageing, suggesting that well-being and QoL are maintained through the adaptive psychological processes of selection, optimisation and compensation [16] but that accelerating functional decline in old-old age pushes the limits of adaptive psychological capacity, resulting in lower subjective well-being [17]. This was reflected in the distinct psychological profiles observed in the oldest participants within their own study [18].…”
Section: Introductionmentioning
confidence: 99%
“…Böttger et al, 2002;Csibra et al, 2000;Yordanova et al, 2000Yordanova et al, , 2002, for examples the of the few gamma-band studies with developmental or aging samples). Therefore, the current study adopts a lifespan perspective (Baltes et al, 1977(Baltes et al, , 1999Craik and Bialystok, 2006), which assumes that development at neuronal and cognitive levels proceeds through interacting influences of maturation, past experience, learning, and senescence (Baltes et al, 2006;Lindenberger et al, 2007). A direct comparison of children, younger, and older adults while performing simple visual discrimination would provide the opportunity for uncovering mechanisms of neuronal communication by taking into account how the assumed mechanisms (i.e., temporal synchronization patterns) may change across different life periods.…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that sensory and sensorimotor abilities decline in the course of normative aging [54,57]. As well, extensive coverage of the normative age-related differences, changes, and continuities in cognitive and intellectual abilities is widely available [10,21]. Rather than reviewing these bodies of literature, we will focus selectively on empirical and theoretical work that has addressed the linkages between these domains with respect to adult development.…”
mentioning
confidence: 99%